Implementation of a program for the analysis of the costs of equipments' maintenance until the end of their useful life - Pedro, I. (2011)
Companies face nowadays a very competitive environment and they have to be well managed to remain sustainable. For being sustainable the company needs either to increase its prices over time or has to reduce the amount of expenses. Reducing costs may be the best option once the global market is very competitive. This work results from the intention of a company (ME-Construction Company) to get a tool to support the decisions related to the equipment management. The aim is to create a model for the analysis of the costs resulting from using MEConstruction Company’s equipments. The studied case is real. This model is the Life Cycle Cost complemented by the Net Present Value and Equivalent Annual Cost. It is worked on a representative sample of the equipment of the company. The application of this model allows the manager to have the estimating tools which may support and justify his decisions in the company. During the equipment’s lifetime, he may have the right perception of the evolution of the expenses and income. The company should develop an equipment costing methodology as much effective as possible in order to consider the expenses that are not included in the equipment value and to consider the equipments which release less greenhouse gases contributing to reduce the global greenhouse effect.